2018
DOI: 10.29399/npa.22924
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing at Workplace - Psychological Trauma and Documentation of Psychiatric Symptoms

Abstract: Objectives: Mobbing at the workplace refers to such cases as verbal harassment, aggressive words, sarcasm, slander or social isolation repeatedly targeted at a specific person at a specific period of time.Previous studies indicate that wellness and health of the victims who have been subjected to mobbing at workplace were affected adversely. Recently, there has been an increase in mobbing cases in Turkey. The purpose of the present study is to identify the features of trauma and analyse the development of ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
2
17
0
3
Order By: Relevance
“…The prevalence was significantly higher compared to the non-exposed patients (60.0%). These results are similar to findings from a study performed on out-patient clinics in Turkey, where 78.5% of patients exposed to bullying could be diagnosed with MDD in accordance with criteria from DSM-IV-TR (Tatar and Yüksel, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence was significantly higher compared to the non-exposed patients (60.0%). These results are similar to findings from a study performed on out-patient clinics in Turkey, where 78.5% of patients exposed to bullying could be diagnosed with MDD in accordance with criteria from DSM-IV-TR (Tatar and Yüksel, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…This prevalence is also quite high compared to healthcare workers in Europe, a sector known for having high prevalence of bullying, where a systematic review by Lever et al (2019) found a mean prevalence of 18.4%. In a sample of patients receiving psychiatric care for workplace traumas in out-patient clinics in Turkey, as many as 43.3% reported exposure to workplace bulling (Tatar and Yüksel, 2019). Prevalence rates estimated from measure of exposure to negative acts such as the NAQ-R or S-NAQ often varies between 10.0 and 17.0% in other countries (Zapf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PTSD and response to bullying victimization share similar manifestations, e.g. distressing emotions, functional impairment and physiological arousal ( Tatar and Yüksel, 2019 ), there is limited data on the association between these phenomena in nurses employed in highly stressful work environments, such as emergency departments (EDs) or intensive care units (ICUs) ( Mealer et al, 2012 ). Previous studies have identified the link between PTSD symptoms and exposure to workplace bullying, however in different populations, i.e.…”
Section: Introductionmentioning
confidence: 99%